2021
DOI: 10.1186/s12967-021-03193-7
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and validation of in-house cryopreserved CAR/TCR-T cell flow cytometry quality control

Abstract: Background Chimeric antigen receptor (CAR) or T-cell receptor (TCR) engineered T-cell therapy has recently emerged as a promising adoptive immunotherapy approach for the treatment of hematologic malignancies and solid tumors. Multiparametric flow cytometry-based assays play a critical role in monitoring cellular manufacturing steps. Since manufacturing CAR/TCR T-cell products must be in compliance with current good manufacturing practices (cGMP), a standard or quality control for flow cytometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Combined with GTEx dataset to evaluated the expression levels of 14 differentially expressed CTAs, we found that CT83 (KK-LC-1) and ZNF165 were expressed at low levels in normal human tissues (with the exception of testis tissue). To date, KK-LC-1 has already been used as immunotherapeutic target that has attempted to produce anti-tumor immune response by using TCR-T, CAR-T vaccines [32,33]. Moreover, we identified that the different mutation profiles of CTAs in both eastern and western GC populations, and found out that the TMB scores in the mutation type of the majority of mutated CTA genes were significantly higher than those in the wild type.…”
Section: Discussionmentioning
confidence: 88%
“…Combined with GTEx dataset to evaluated the expression levels of 14 differentially expressed CTAs, we found that CT83 (KK-LC-1) and ZNF165 were expressed at low levels in normal human tissues (with the exception of testis tissue). To date, KK-LC-1 has already been used as immunotherapeutic target that has attempted to produce anti-tumor immune response by using TCR-T, CAR-T vaccines [32,33]. Moreover, we identified that the different mutation profiles of CTAs in both eastern and western GC populations, and found out that the TMB scores in the mutation type of the majority of mutated CTA genes were significantly higher than those in the wild type.…”
Section: Discussionmentioning
confidence: 88%
“…38,39 This becomes even more relevant when discussing CAR-T cell therapy cryopreservation, as it is important to ensure that these act efficiently and conserve high viabilities. 40,41 Studies have shown lower cell viability and cytokine expression, 42 lower surface marker expression, 43 upregulation of apoptosis-associated gene expression 7 and lower cellular expansion after thawing compared to fresh CAR-T products. 44 Although results vary along studies, their cryopreservation is usually supported, as evidenced by the FDA approval of cryopreserved CAR-T products, which allow their centralised manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Cell count and viability (CCV) measurement is perhaps the most fundamental analytical method used in development and execution of manufacturing processes for cell therapy and regenerative medicine. CCV is also a routine release specification for almost all cell therapy products and is used to determine populations to densities, potency assays, functional cell assays, ELISA and Gene modification assays [1][2][3]. Therefore, the choice and implementation of cell counting methodology can play a pivotal role in the development of manufacturing processes, and eventually commercialization of cell therapies.…”
Section: Introductionmentioning
confidence: 99%